A simplified settlement prediction method for piled rafts in clay. Issue 2 (7th April 2022) - Bhartiya, Priyanka; Basu, Dipanjan; Chakraborty, Tanusree
Abstract : A method for the estimation of the non-linear, time-dependent settlement of piled raft foundations (PRFs) embedded in saturated clayey soils subjected to uniformly distributed load under the single-drainage condition was developed. A total of 20 different rectangular PRFs resting on four different types of normally consolidated to moderately overconsolidated clays (overconsolidation ratios of 1, 2 and 5) were analysed to quantify their short- and long-term settlements. Rigorous three-dimensional, elasto-plastic finite-element (FE) analyses were performed with the critical-state-based modified Cam Clay soil constitutive model. Biot's coupled consolidation theory was used to model the time-dependent dissipation of excess pore pressure under the single-drainage condition. The FE analysis results were used to investigate systematically the influence of time and various soil and PRF parameters on the settlement responses of piled rafts. Fitted equations correlating PRF settlements and the degree of consolidation with various influencing parameters were developed. The proposed equations predicted the immediate and primary consolidation settlements and the degree of consolidation with reasonable accuracy and can be used in initial design stages.